2020
DOI: 10.1186/s13058-020-01297-4
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in CD8+ T cell infiltration in breast tumors from Black and White women

Abstract: Background: African American/Black women with breast cancer have poorer survival than White women, and this disparity persists even after adjusting for non-biological factors. Differences in tumor immune biology have been reported between Black and White women, and the tumor immune milieu could potentially drive racial differences in breast cancer etiology and outcome. Methods: We examined the association of CD8 + cytotoxic T cells with clinical-pathological variables in the Women's Circle of Health Study (WCH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 49 publications
4
32
1
Order By: Relevance
“…AA women exhibit higher tumor-infiltrating CD8 + T cell density compared to white women indicating a potential involvement of immune landscape in racial disparity. Although no clear association is observed between CD8 + T cell density and overall survival, higher CD8 + T cell density in AA-TNBC associate with better overall survival which is paradoxical ( Abdou et al, 2020 ). Interestingly, exosome analysis shows higher expression of exosomal-Annexin 2 (exo-AnxA2) in the sera of AA women with TNBC indicating its potential role in angiogenesis and tumor promotion ( Chaudhary et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…AA women exhibit higher tumor-infiltrating CD8 + T cell density compared to white women indicating a potential involvement of immune landscape in racial disparity. Although no clear association is observed between CD8 + T cell density and overall survival, higher CD8 + T cell density in AA-TNBC associate with better overall survival which is paradoxical ( Abdou et al, 2020 ). Interestingly, exosome analysis shows higher expression of exosomal-Annexin 2 (exo-AnxA2) in the sera of AA women with TNBC indicating its potential role in angiogenesis and tumor promotion ( Chaudhary et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer TILs include a large portion of T cells (CD8+ and CD4+ T cells), and smaller portions of B cells and NK cells [ 83 ]. CD8+ T cell density is higher in AA breast tumors compared to EA women and is associated with improved clinical outcomes in the AA population [ 84 ]. While increased CD8+ T cell density is linked to an overall increase in breast cancer patient survival rates, CD8+ T cell exhaustion contributes to a poor prognosis due to decreased effector cytokine production.…”
Section: Race Tme and Tumor Sitementioning
confidence: 99%
“…TILs are predominantly comprised of B cells, T cells, and NK cells, playing a crucial role in antitumor immune response [ 26 ]. AA women with the Basal/TNBC subtypes are reported to show more regulatory T cells (Tregs), while there are more CD8 + lymphocytes only in the luminal subtypes of breast cancer in AA women [ 27 , 28 ]. A higher number CD8 + T cells is indicative of a favorable response to neoadjuvant therapy in various molecular subtypes of breast cancer [ 25 , 29 , 30 ].…”
Section: Racial Disparity In the Composition Of Breast Cancer Tmementioning
confidence: 99%
“…A higher number CD8 + T cells is indicative of a favorable response to neoadjuvant therapy in various molecular subtypes of breast cancer [ 25 , 29 , 30 ]. Furthermore, immunohistochemical staining of CD8 + T cells revealed that a higher percentage of CD8 + T cells are recruited in the tumor of AA breast cancer patients compared to CA women with breast cancer, which is suggestive of the mounting of strong immune response [ 27 ]. Other groups have also identified differential TIL in TNBC between AA and CA [ 23 , 24 ].…”
Section: Racial Disparity In the Composition Of Breast Cancer Tmementioning
confidence: 99%